Pengaruh Proses Pengelasan SMAW (Shielded Metal Arc Welding) Terhadap Laju Korosi Material Baja ST 37 Pada Daerah HAZ Dan Base Metal Dengan Variasi Ampere 120,160,200 - Putra, Deddy Kuswandi, Agus Dwi Anggono, ST, M.Eng, Ph.D (2017)
Corrosion is gradual material damage caused by chemical reaction with the environment. The corrosion processes can be caused by both chemical reaction and electrochemical reaction process. Gradual destruction caused by corrosion can be controlled or slow down the process by several methods. This research was conducted to investigate the effect of welding method of SMAW (Shielded Metal Arc Welding) to the corrosion rate of the steel ST37. The welding process was carried out in the variation of 120, 160 and 200 Ampere. The area of investigation was in the HAZ and base metal. Corrosion rate was done by using NaCl solution for the specimen as long as 48 hours. The result shows that the corrosion rate was decrease when it used high current. The HAZ of the specimen using 120 A was delivered the highest 0.770 mm/Y corrosion rate. The lowest corrosion rate was 0.6513 mm/Y delivered by 200 A of welding process